Disasters in Malaysia: tomorrow is a mystery - Duraisamy, Youventharan; Mohamad Idris, Ali; Noram Irwan, Ramli; Rokiah, Othman; Mohd Arif, Sulaiman (Penerbit UMP, 2018)
Lately there are high occurrences of natural disasters in Malaysia. Does it have anything to do with earth been suffering from extreme weather conditions or could be any other reasons to it. Some scientists say that the temperature of the Earth is on the rise, which results in global warming. As the consequence to that, scientific theory also explains how global warming causes icebergs to melt in the colder regions, which in turn causes natural disasters around the world. If these theories are real, can we humans manage and control the climate changes as well as mitigate the post disasters issues more efficiently? Can this unwanted natural phenomenon be stopped for good if we can predict the occurrence more accurately and the effects reversible? To what extend all these disasters impaired the livelihood of fellow Malaysian? With all these questions in mind, this book has been drafted to give some useful insights into the most traditional and the typical disasters in Malaysian land. Listed below are some examples of the natural disasters and the extreme weather conditions that have occurred in Malaysia, over the past year: